2019
DOI: 10.1111/jcmm.14791
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circFOXO3 promotes prostate cancer progression through sponging miR‐29a‐3p

Abstract: Circular RNA FOXO3 (CircFOXO3, also termed as Hsa_circ_0006404) is derived from exon 2 of forkhead box O3 (FOXO3) gene, and abnormal expression is shown in different diseases. However, whether circFOXO3 plays important roles in tumorigenesis and progression of prostate cancer (PCa) remains unclear. In this study, we found that circFOXO3 was up‐regulated in both PCa tissues and serum samples. Moreover, circFOXO3 was positively correlated with the Gleason score in PCa samples. CircFOXO3 was observed to be up‐reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
110
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(114 citation statements)
references
References 31 publications
2
110
2
Order By: Relevance
“…Circ 000984 promotes cell proliferation and metastasis in NSCLC by modulating Wnt/β-catenin pathway [23]. CircRNA circFOXO3 promotes the prostate cancer progression [24]. The down-regulation of circRNA ciRS-7 [25] or circ 0067934 [26] blocks cell proliferation, migration and invasion of NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Circ 000984 promotes cell proliferation and metastasis in NSCLC by modulating Wnt/β-catenin pathway [23]. CircRNA circFOXO3 promotes the prostate cancer progression [24]. The down-regulation of circRNA ciRS-7 [25] or circ 0067934 [26] blocks cell proliferation, migration and invasion of NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Kong et al disclosed that circFOXO3 acted as a sponge of miR-29a-3p to facilitate prostate cancer cell proliferation and repressed apoptosis. 27 In this paper, the influences of circ-ZNF652 silencing on HCC cell growth, metastasis and glycolysis were all weakened by the inhibition of miR-29a-3p, indicating that circ-ZNF652 could sponge miR-29a-3p to modulate HCC progression. In HCC, miR-29a-3p could hamper cell growth and migration by targeting IGF1R.…”
Section: Discussionmentioning
confidence: 67%
“…Although previous studies (Chen et al, 2017;Meng et al, 2017;Kristensen et al, 2018) have reported circRNA miRNA sponge functions in many types of cancers, little is known about the role of circRNAs in PCa. Kong et al (2020) showed that hsa_circ_0006404 promoted PCa progression through sponging miR-29a-3p, while Cai et al (2019) demonstrated that circHIPK3 overexpression accelerated the proliferation and invasion of PCa cells by regulating miRNA-339-3p. Additionally, Wang et al (2019) revealed that circRNA ITCH suppressed PCa progression by upregulating HOXB13 expression through sponging miR-17-5p.…”
Section: Discussionmentioning
confidence: 99%